BANQUET PERFORMANCE IN SUPPORTING BUSINESS AT PULLMAN SUDIRMAN JAKARTA HOTEL - Nugraha, Rizki Nurul; Aulia, Almaura Nur; Nehemia, Claudia Simponi (Akademi Komunitas MAPINDO, 2022)
Banquet section is one part of the Food and Beverage department which has an important role in the hotel business to earn revenue for the hotel through the services it sells, such as food, beverage and function room sales, because it can accommodate a large number of guests. That way all hotels must have a banquet section that is nimble and capable in carrying out their duties, including the Pullman Sudirman hotel. In this case the researcher uses a qualitative method with a descriptive format. Qualitative methods aim to describe, summarize various circumstances, situations, or various events in the social sphere. Data collection techniques will be carried out using the interview method, the researcher hopes to get detailed, honest, and intense data related to the performance of the Pullman Sudirman Hotel banquet department employees. From the results of an interview with the Pullman Sudirman Hotel supervisor, it was explained that the Banquet at this Hotel is very supportive of business because this department has an influence in increasing turnover/revenue which is very large compared to other restaurants. Keywords: Banquet Performance, Hotel Business, Pullman Sudirman